Corporate Regulations and Quality of Financial Reporting: A Proposed Study - Ibrahim, Mohd Yussoff; Ahmad, Ayoib Che; Johl, Satirenjit Kaur; Rahman, Haseeb Ur (International Journal of Economics and Financial Issues, 2016)
Most of the corporate demises evidenced poor quality of financial information reporting. Besides others, this is due to inefficiency of board which couldn’t ensure effective monitoring of management. Subsequently, the regulators have focused independence of the board among others. Accordingly, the recently introduced Malaysian Code on corporate governance (MCCG 2012) also recommended independence of the board like many other CG regulations around the world. Therefore, this paper proposes to examine few attributes of the new code regarding independence of the board in relation to quality of financial information reporting. These attributes includes separate leadership, independent chair and proportion of independent directors on board and nomination committee. To find distinct impact of the code, the paper divides study period into 2 years pre (2010-11) and 2 years post (2013-14) context of the code. The proposed study will fill the literature gap particularly in developing economies like Malaysia. The study will also provide important guidance for regulators, shareholders, security commission, Bursa Malaysia and other stakeholders in Malaysia. Keywords: Corporate Governance, Quality of Financial Information Reporting, Non-Financial Malaysian Listed Companies, MCCG 2012 JEL Classification: 224